Diagnostic Accuracy of T-SPOT.TB Assay for Tuberculous Meningitis: An Updated Meta-Analysis - Luo, Ying; Xue, Ying; Guo, Xueyun; Lin, Qun; Mao, Liyan; Tang, Guoxing; Song, Huijuan; Wang, Feng; Sun, Ziyong (Frontiers in Neurology, 2020)
Background The role of T-SPOT.TB (T-SPOT) assay for tuberculous meningitis (TBM) diagnosis has not been fully assessed. Here, we conducted an updated meta-analysis to evaluate the diagnostic accuracy of peripheral blood (PB) T-SPOT and cerebrospinal fluid (CSF) T-SPOT for diagnosing TBM. Methods Relevant studies in the PubMed database, EmBase database, Cochrane database, Scopus database, Google scholar, China national knowledge internet and Wan-Fang database were retrieved from August 1, 2005 to June 22, 2020. Statistical analysis was performed using Stata, Revman and Meta-Disc software. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), summary receiver operating characteristic (SROC) curves and the area under the curve (AUC) were determined and analyzed. Results A total of twenty-seven studies were eligible for inclusion within the meta-analysis. The pooled sensitivity and specificity of PB T-SPOT for TBM diagnosis were 0.78 (95% CI, 0.76-0.81) and 0.68 (95% CI, 0.66-0.71), respectively, while the pooled PLR, NLR and DOR were 2.80 (95% CI, 2.29-3.42), 0.32 (95% CI, 0.27-0.38) and 10.08 (95% CI, 7.21-14.08), respectively. On the other hand, the pooled sensitivity and specificity of CSF T-SPOT on diagnosing TBM were 0.76 (95% CI, 0.72-0.80) and 0.88 (95% CI, 0.85-0.90), respectively, while the pooled PLR, NLR and DOR were 5.92 (95% CI, 4.25-8.25), 0.28 (95% CI, 0.21-0.39) and 29.05 (95% CI, 16.40-51.45), respectively. The area under the SROC curve of PB T-SPOT and CSF T-SPOT for TBM diagnosis were 0.83 (95% CI, 0.80-0.86) and 0.92 (95% CI, 0.89-0.94), respectively. Conclusions CSF T-SPOT showed a higher specificity compared with PB T-SPOT for diagnosing TBM. Both two T-SPOT assays have considerable potential in improving the diagnosis of TBM. Furthermore, the standardization of the operating procedure is further needed when performing CSF T-SPOT.